Bone marrow necrosis in a patient with non-Hodgkin lymphoma - (:unkn) unknown (My University, 2004)
Bone marrow necrosis is a rare but ominous finding in various malignant and nonmalignant disorders. It is usually a postmortem diagnosis, but with the advent of modern imaging methods and clinical suspicion, bone marrow necrosis can be diagnosed as antemortem, especially in malignant disorders. We report a 60-years old man with newly diagnosed non-Hodgkin lymphoma presenting with anemia and very high level of alkaline phosphatase. On bone marrow biopsy, it was noted with extensive BMN characterized by cellular debris with indistinct cellular margin and abnormally eosinophilic staining cytoplasm. Despite the prompt institution of aggressive chemotherapy, one week later, liver function tests gradually deteriorated and the patient succumbed. Given the high mortality rate, when the bone marrow necrosis is suspected especially in a patient with malignancy, disease specific treatment and vigorous supportive measures should be immediately commenced.
Keywords: Bone marrow necrosis; Hematologic malignancy